Components and structure of scientific support systems of athlete's preparation to Olympic Games. - Pavlenko І.O (Kharkov National Pedagogical University, 2011)
The factors, which determine components and structure of scientific support systems of athlete's preparation in Olympic sports are systematizing. It was marking out the six components of the scientific support's realization: sports pedagogical, biological, psychological, informational, material and organizational. The role of components' function in development and realization of innovations, their correlation and interdependence had been shown. Directions of development and realization in practice of the system of sporting preparation are recommended by sporting-pedagogical technologies. The complex of medical biological measures which are directed on saving of the state of health and increase of functional possibilities of sportsmen is certain.